2004
DOI: 10.1021/op034157y
|View full text |Cite
|
Sign up to set email alerts
|

An Improved and Single-Pot Process for the Production of Pantoprazole Substantially Free from Sulfone Impurity

Abstract: Pantoprazole (1), a substituted benzimidazole derivative, is an irreversible proton pump inhibitor, essentially used for the prevention and treatment of gastric acid-related diseases. The process for its preparation generally suffers from the drawback of producing a potential sulfone impurity (5). The present work details a report of the journey towards the development of a simple, single-pot process for the production of pantoprazole, substantially free from sulfone impurity (5). The detailed study of the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…No reasonable mechanism for their formation has been provided. 10 In some methods, however, a mixture of dichloromethane and methanol is used with peracids 11 or with sodium hypochlorite 12 for the oxidation of the thioether wherein methanol may be converted to formaldehyde and formic acid, possibly resulting in Eschweiler–Clarke reaction 13 and affording trace amounts of the N-2 and N-7 methylated byproducts. Perhaps more importantly, commercial methanol may contain trace quantities of formaldehyde, 14 which is subsequently converted to formic acid in the presence of sodium hydroxide.…”
Section: Resultsmentioning
confidence: 99%
“…No reasonable mechanism for their formation has been provided. 10 In some methods, however, a mixture of dichloromethane and methanol is used with peracids 11 or with sodium hypochlorite 12 for the oxidation of the thioether wherein methanol may be converted to formaldehyde and formic acid, possibly resulting in Eschweiler–Clarke reaction 13 and affording trace amounts of the N-2 and N-7 methylated byproducts. Perhaps more importantly, commercial methanol may contain trace quantities of formaldehyde, 14 which is subsequently converted to formic acid in the presence of sodium hydroxide.…”
Section: Resultsmentioning
confidence: 99%
“…We found that there is no criticality of pH range and solvent except temperature of the reaction in the formation of 6 , as is claimed by various researchers. 13,17 Meanwhile, isolation of the compound by pH adjustment in water alone proved problematic. The nature of the solid obtained after pH adjustment was found to be gummy; therefore, a suitable solvent for the isolation of 5 from aqueous layer was required.…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of sulfide impurity is not critical for the final quality of the product because it can be efficiently removed as it has no inclination toward sodium salt formation. 13 The present process produces the pantoprazole containing not more than 0.2% (w/w by HPLC) of total impurities.…”
Section: Introductionmentioning
confidence: 92%
“…The sesquihydrate was synthesized by dissolving the pantaprazole free base [17] (50 g, 0.130 mol) in a mixture of sodium hydroxide (5.4 g, 0.134 mol) (The Andhra Sugars Ltd., Tanuku, India), de-ionized water (10 mL) and 350 mL of tetra hydro furan (THF) (TCC chemicals, Taiwan), followed by precipitation of salt by addition of 400 mL dichloromethane (Standard Laboratories, Hyderabad, India) as an anti-solvent to the resulting mixture at 25-35 • C. Finally, it was cooled to 0-5 • C and the precipitated solid was filtered to obtain the sesquihydrate as a fine solid material. The polymorphic purity was confirmed by PXRD, DSC and FT-IR.…”
Section: Methodsmentioning
confidence: 99%